Recovering Value in Distressed Companies: A Case Study of Tuban Petrochemical Industries and its Subsidiaries - Hilman Prakosa (Syntax Literate, 2023)
This study aims to investigate the restructuring process of PT Tuban Petrochemical Industries (Tuban Petro) and its subsidiaries, formerly owned by the ex-National Bank Restructuring Agency (IBRA). The study also seeks to examine strategic initiatives aimed at increasing competitiveness and effecting leadership, organizational and stakeholder changes to achieve value recovery. This qualitative study employs an explanatory case study approach. Data were collected through unstructured interviews and archival studies. The market multiples approach was used to measure the estimated stock value. The results indicate that the turnaround strategies and efforts successfully unlocked value during the distressing conditions. Strategies for restoring competitiveness, changing leadership and organization, and gaining stakeholder support were crucial for achieving value recovery. In distressed companies, shareholders, suppliers, distributors, and creditors play a significant role in restoring competitiveness and driving changes in leadership and organization. The estimated value recovery shows that the turnaround was implemented through a strategy with costs and a long value recovery time. This study fills a gap in the literature as few studies have examined the restructuring of ex-IBRA assets due to limited access to comprehensive information. The findings provide an alternative evaluation of the restructuring process and the strategies implemented, which can inform future strategies for similar distressed companies facing crises.